PENERAPAN MODEL BENEISH M-SCORE DAN ANALISIS RASIO UNTUK MENDETEKSI KECURANGAN LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Yang Mendapat Suspend Dari BEI Tahun 2018) - Yuyun Fadilah; Maslichah Maslichah; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThe purpose of this study was to determine the effect of the Beneish M-Score Model variables from aspects of Days Sales in Receivable Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), Depreciation Index (DEPI) , Sales General and Administrative Expenses Index (SGAI), Leverage Index (LVGI), Total Accruals to Total Assets (TATA) and Ratio Analysis from aspects of Liquidity Ratios, Profitability Ratios, Activity Ratios, Leverage Ratios to the detection of Financial Report Fraud. The method of data collection is documentation. The sample used was a publicly listed company listed on the Indonesia Stock Exchange 2015-2016 and received suspensions from the Indonesia Stock Exchange in 2018 as many as 32 companies. The results of this study are that publicly listed companies that get suspensions from the IDX in 2015-2016 are classified as manipulators, there are 94.54% and non manipulators 5.46%.Keywords: Beneish M-Score Model, Ratio Analysis, Fraud of Financial Statements.